Integrated nutrient management as a sustainable strategy to recover a decayed Pear (Pyrus communis) orchard - Poblete, Hugo (2021)
Integrated Nutrition Management (INM) is a concept developed during the last decade in fruit agroecosystems based on the application of organic matter, biostimulants, and adjusted chemical fertilization to improve soil quality, plant rhizogenesis, and nutrition. Nevertheless, there are few studies on the application of the INM concept on the recovery of decayed orchards. The present study was focused on the evaluation of the effects of INM on soil and plant quality changes as recovery indicators of a decayed pear orchard. Two treatments (T1: conventional, T2: INM) were evaluated under three tree vigor levels, during two growing seasons. Old pear trees were used in a factorial experiment of two treatments (control and INM) x three vigor levels, based on a previous aerial Normalized Difference Vegetation Index (NDVI) image. Soil properties, nutrient leaf contents, and NDVI were evaluated. Soil chemical and biological properties and their spatial variability were determined after two and five years of treatment application, respectively. The INM improved β-glucosidase activity, reduced bulk density, and increased soil porosity. Furthermore, nutrient indices (NDVI x N, K, Ca, Mg, Cu, Fe, and B) were significantly increased under INM. After two years, soil chemical properties and root density were improved by INM. A significantly higher yield, soil organic matter, soluble C, and dehydrogenase activity was observed with INM after five growing seasons. The results indicated that INM is a sustainable alternative for recovering decayed orchards, through the inclusion of good-quality organic matter within the management program.